Strengthening food policy through gender and intrahousehold analysis: impact assessment of IFPRI multicountry research - Jackson, Cecile (International Food Policy Research Institute, 2005)
This assessment focuses on IFPRI’s research program, Strengthening Food Policy through Intrahousehold Analysis,” within the Food Consumption and Nutrition Division (FCND). The program was initiated in 1992, formally began in 1994, and was completed in 2003. Research undertaken in the program was complex, involving work in several countries and taking on challenging new research issues of great potential policy relevance, within a rapidly changing environment. The objectives of the program were to document intrahousehold resource allocation patterns; develop economic models and data collection methods necessary to investigate determinants of intrahousehold resource allocations; establish the relevance of these patterns and models for food policy; evaluate the benefits relative to additional costs of data collection at the intrahousehold level, develop guidelines for a priori expectations on intrahousehold issues, and manage outreach through training materials and publications geared to the range of research users.